Is there scope for gains from revenue-neutral labor tax reforms with flexible outsourcing? - Erkki Koskela; Panu Poutvaara (Institute for the Study of Labor (IZA), 2009)
We study the effects of revenue-neutral labor tax reforms in an imperfectly competitive domestic labor market under Nash wage bargaining and flexible outsourcing. A revenue-neutral increase in the wage tax progression will decrease the negotiated wage rate, increase domestic labor demand and decrease international outsourcing. In the presence of wage tax exemption, a lower payroll tax and a higher wage tax will increase domestic labor demand and decrease international outsourcing. The effect on the negotiated wage rate is positive with sufficiently strong labor market imperfections, and ambiguous with sufficiently weak labor market imperfections.
urn:nbn:de:101:1-2009021683
Keywords: H11; H22; J41; J51; 330; Flexible outsourcing; wage bargaining; employment; tax-revenue neutral labor tax reforms; Lohnsteuer; Steuerreform; Steuerinzidenz; Outsourcing; Lohnverhandlungen; Beschäftigungseffekt; Theorie